2011
DOI: 10.1007/s10508-011-9885-3
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Monogamy Among Gay Male Couples in a Community Survey: Implications for Mental Health and Sexual Risk

Abstract: Researchers have documented the psychological and physical health benefits of being in a relationship among heterosexuals, although there has been limited research to examine such benefits among gay and bisexual men. Gay and bisexual men demonstrate considerable variety in the nature of their relationships, particularly in terms of the degree to which they are monogamous. In order to better understand the psychological and behavioral impact of same-sex relationships on the health of gay and bisexual men, demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 48 publications
(51 reference statements)
5
123
2
1
Order By: Relevance
“…This finding is in contrast with outcomes from studies of heterosexual men and women, which have generally found no significant link between income and concurrency [28,39]. A recent study of relationship arrangements among gay men also found no link between income and whether men were in monogamous or non-monogamous relationships [13]. These studies, however, were conducted in the United States and there may be differences between the two countries.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This finding is in contrast with outcomes from studies of heterosexual men and women, which have generally found no significant link between income and concurrency [28,39]. A recent study of relationship arrangements among gay men also found no link between income and whether men were in monogamous or non-monogamous relationships [13]. These studies, however, were conducted in the United States and there may be differences between the two countries.…”
Section: Discussionmentioning
confidence: 67%
“…In most studies, approximately 40-50% report being in a regular relationship [9][10][11], but many of these relationships are likely to be non-monogamous. For example, open relationships, whereby men negotiate agreements with their primary partner to allow one or both of them to have sex with other men, appear to be more common than among heterosexual men and women [12][13][14]. Gay men also account for the largest proportion of HIV infections in developed countries [15] and have disproportionately high rates of other STIs [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Next, following a similar categorization scheme used in other research (Hosking, 2013;LaSala, 2004a), participants indicated which of three descriptions best described their current sexual agreement: closed ("It is NOT okay for you or your partner to have sexual contact with men outside your relationship"), threesome-only ("It is okay for you and your partner to have sexual contact with men outside your relationship, but ONLY in threesomes or groups that include BOTH of you"), or open ("It is okay for you and your partner to have sexual contact with men outside your relationship"). As mentioned earlier, the threesome-only category is referred to as "monogamish" (Parsons et al, 2011) throughout this article. There was no "other" response option for this question; however, an optional free response question allowed participants to provide further details or qualifications regarding their agreement.…”
Section: Methodsmentioning
confidence: 99%
“…33 Other pieces of research have noted that MSM who reported being in a monogamous relationship were less likely to have used substances with sex compared to those who were either single or in some type of a nonmonogamous relationship. [32][33][34] Although these few studies provide some insight about male couples' use of substances (with sex), additional research with male couples is needed because: (1) substance use with sex is fairly common among MSM, (2) substance use and UAS are strongly correlated and may increase the likelihood of HIV acquisition, (3) substance use may impair adherence to ART among those living with HIV, (4) many US male couples practice UAS within their relationship 35,36 , and (5) between one and two thirds of MSM in the USA acquire HIV from their main partners while in a same-sex relationship (e.g., male couples). 37,38 Given the public health relevance for studying how substance use may affect male couples' health (e.g., HIV prevention and adherence), research is lacking on how dynamics of their relationships may be impacted by their use of substances with sex.…”
Section: Introductionmentioning
confidence: 99%